CODESRIA Bulletin Online, No. 4, April 2023 - BOOK REVIEW: Invisible Trillions: A Threat to Global Prosperity * - Dipeolu, Adeyemi (CODESRIA Bulletin, 2023)
I always like to start any discussion on the subject of illicit financial flows in Africa by recalling the story of how the fight gained momentum on the continent. In 2011, we were holding the annual Conference of African Ministers of Finance, Planning and Economic Development of the UN Economic Commission for Africa (ECA), in Lilongwe, Malawi. As ECA Chief of Staff I was part of a team directed by the Executive Secretary to find a small hall as a venue for a side event, with the discussions to be led by an elderly American gentleman. We looked for a hall that would take 20 to 30 people but this proved quite difficult because all the small halls had already been allocated to sub-committees and other events of the Conference. When all efforts failed, we eventually settled on using the main Plenary Hall, which would be empty because participants would be engaged in the sub-committees and other peripheral events. The Plenary Hall was built to take at least 500 people, representing all 54 member states of the ECA, partner agencies, observer countries and organisations. We felt that it would be awkward to hold a meeting of 20 to 30 people in such a large room but agreed that since we did not have a choice we would encourage participants to seat themselves in the centre of the first few rows. When the event started, we were awestruck. The Plenary Hall was full to the brim, with people standing on all sides. This was how we learnt that there was a thirst, nay hunger, to know more about the phenomenon of illicit financial flows and their impact on Africa. The ministers passed a resolution following that event, and – as they say – the rest is now history. The gentleman who sparked this huge interest in illicit financial flows in Africa was Raymond W. Baker, who had made great efforts to bring the dangers of illicit financial flows to the attention of African governments and civil society organisations and had been appointed to the AU/ECA High Level Panel (HLP) on Illicit Financial Flows from Africa. The work of the HLP showed clearly the scale of illicit financial flows from Africa and their negative impact on development. Raymond Baker’s new book, Invisible Trillions, has just been published and it throws more light on the work of the High Level Panel, including the fact that the impact of illicit financial flows on African economies goes beyond the financial losses occasioned by such outflows, having a negative effect also on governance and the opportunity cost of lost investments. One very interesting point made by Baker in this new offering, his second in this important area after Capitalism’s Achilles Heel (2005), is that while base erosion and profit shifting may lie behind the desire of multinational corporations to move money out of developing countries, their primary motivation seems to be the conversion of soft to hard currencies, which is greatly enabled by a financial secrecy system. In Invisible Trillions, Baker lays bare the workings of this fast-expanding global financial secrecy system and how it increases inequality and undermines the rule of law in a manner that imperils capitalism and its twin, liberal democracy. Although Baker’s primary focus is the United States, it is clear that the concerns he is expressing apply to the whole world, which is not surprising given the leadership position of the United States in global affairs. Through painstaking, rigorous and detailed research, Mr Baker lays bare the subterfuge that underpins the financial secrecy system and highlights the motives of various actors and enablers, whom he identifies using publicly available yet mostly obscure information, some from legal sources. He shows how multinational corporations, international banks, large legal and accounting firms, criminal networks and complicit governments have erected a system which is underpinned by tax havens and financial secrecy jurisdictions, to hide their wealth. Baker’s purpose, though, is to show that the financial secrecy system has now come to undermine capitalism, which in turn exacerbates inequality and the very foundations of liberal democracy. Quite refreshingly, despite amassing evidence of the scale and spread of commercial evasions, criminal behaviour and corrupt practices, Raymond Baker offers prescriptions about what can be done to stop this tidal wave. He strongly believes that political action can stop the financial secrecy system in its tracks, just as the US Patriot Act put an end to the existence of shell banks. In short, Baker calls for actions to ‘deconstruct secrecy’, and while acknowledging some progress in this regard he calls for further action to tackle disguised corporations, opting for company-by-company reporting over country-by-country reporting and for strong action against trade falsification. It is no wonder that Larry Diamond (who wrote the Foreword) agrees with Baker that ‘Only radical improvements across the globe in financial transparency and in regulatory capacity and integrity can break this cycle of political decay and despair.’ Invisible Trillions is a well-timed contribution to the current debate about the crisis of capitalism and the dangers it portends for democracy. The influential FT columnist, Martin Wolf, has also been writing on this topic, making essentially the same point as Baker, that the survival of democratic capitalism depends on widely shared prosperity. If global financial secrecy promotes greater inequality then indeed there is cause for concern about the health of democratic capitalism. Invisible Trillions is an invaluable contribution to this discourse and the world must heed Raymond Baker. Note * First version published in https://www.thecable.ng/invisible-trillions-a-threat-to-global-prosperity